Risk assessment of the development of the endoleak after evar. - Vlasenko O. А. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Treatment of aortic aneurysms is one of the most difficult problems in angiology. The ending of the development of the disease is the rupture of the aneurysm with high mortality. EVAR is a minimally invasive method of treating aneurysms. However, even today its high immediate effectiveness is leveled by an increased need for repeated interventions in the long-term period. The main cause of repeated interventions is endoleaks of blood in the aneurysmal sac (AS), which causes its increase and the risk of rupture. Objective. Develop methods for predicting the risk of EF after endoprosthetics of the infrarenal aorta by analyzing the results of the study of the morphology of the anterior wall of the common femoral artery (CFA). In the course of the study, an original method for the in vivo diagnosis and prognosis of the pathological process in the aortic wall with its aneurysmal lesion was developed and used, including the taking of material during endoprosthesis. The method differs in that in order to determine pathomorphology, in order to establish the etiology of the development of an aortic aneurysm, a histological study is carried out not directly on the aortic wall, but on the CFA wall, as a large elastic artery. Morphological investigations of CFA were performed in 38 patients. The average age of patients was 66.1 ± 2.1, among them 2 women and 36 men. Results. The results showed that in 22 cases (57.8%) there were direct signs of atherosclerosis, in 14 cases (36.8%) - manifestations of dystrophic changes, in 2 cases (5.26%) inflammatory reactions prevailed in the pattern of pathology. Statistical analysis showed that there is a stable and reliable relationship between the nature of the morphological changes in the wall of the CFA and the dynamics of the AS size after EVAR. Atherosclerotic changes are characterized by a decrease in AS in 77.7%, while with dystrophic changes, a decrease in AM is observed only in 28.7%, and in 64.2% there are no changes in the size of the bag, or the bag has increased. Conclusion. Morphological studies of the CFA wall in patients make it possible to judge that with the prevailing atherosclerotic changes in the vessel walls by 16.5 times - OR-16.5 (2.79-97.68) increases the probability of AS decrease after endoprosthesis replacement. In case of dystrophic changes, the prognostic assessment is unfavorable - the probability of decreasing AS decreases by 94% - OR = 0.06 (0.01-0.36).